The Opinion of Politic in Nu Online Perspective Principles of Dakwah Journalism on January – September 2023 Edition: (Theo van Leeuwen’s Critical Discourses Analysis) - Musyaffa, Musyaffa; Azara, Ustaza Kaffah; Mahadi, Ujang (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research aims to analyze the implementation of da'wah journalism in political opinions published in the January to September 2023 edition of nu.or.id. This research method was descriptive qualitative with analysis of Theo Van Leeuwen's critical discourse analysis theory, with a focus on the linguistic and semiotic strategies used in political opinion texts. There were five political opinion articles analyzed. The result, namely the implementation of da'wah journalism on political opinions on the nu.or.id website from January to September 2023, has been reflected in various linguistic and semiotic strategies.